Analisis Pengaruh Penggunaan Physical Wedge Filter pada Dose Profile dan Percentage Depth Dose Pesawat Radioterapi Clinax-Cx di Rumah Sakit Universitas Andalas - Alhafiz, Mohammad Randy; Adrial, Rico (Jurnal Fisika Unand, 2025)
A study has been conducted on the effect of using a physical wedge filter on the dose profile and Percentage Depth Dose (PDD) of the CLINAC-CX teletherapy device at Andalas University Hospital. This study aims to determine the shape of the dose profile and PDD curves formed from the use of physical wedges. Measurements were made with variations in photon beam energy (6 MV and 10 MV) and variations in the angle of the physical wedge filter (15°, 30°, 45°, and 60°). Data processing begins by calculating incomplete data from the LINAC using interpolation techniques. The data is then displayed in the form of a curve or graph using Microsoft Excel. The results of the PDD curve measurement showed no significant difference in the curve formed using or without a wedge. The resulting zmax did not differ much from each other, where for a 6 MV beam without a wedge it was 13.8 mm while the average wedge variation was 14.72 mm. The 10 MV beam variation showed a value of 23.4 mm and an average of 24 mm. The dose profile formed is influenced by the use of wedge, the comparison of the smallest and largest symmetry, flatness, and penumbra values. The smallest values ​​at 6 MV irradiation without wedge are respectively 2.1%, 3.1%, 7.1 mm, and 7.3 mm, while the largest with a wedge angle of 60°, 32.4%, 58.3%, 15.8 mm. The wedge factor between 6 MV and 10 MV shows no difference.